(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
INTRODUCTION: Antimicrobial agents were considered as magic bullets and effective tools to combat infection in various therapeutic settings. In conventional antibiotic use, antimicrobials are used for a predetermined period after therapeutic procedure to combat the infection because most often in public hospitals due to lack of maintainance of environmental hygiene & overload of surgical patients fear of SSI (surgical site infection) are more. AIMS AND OBJECTIVES: To study the wound infection rate and recognition and prevention of exogenous and endogenous sources of SSI in laproscopic cholecystectomy, whether long term antibiotics should be given or antibiotics given at the maximum time of concentration are sufficient. MATERIALS AND METHODS: Study size and period: 50 cases, June 2017 to December 2018.Study conducted at: V.S.G.H, Ahmedabad.Single dose of antibiotic, 1 gm ceftriaxone was administered one hour before surgery by IV route & 5 days course, 2 days IV and 3 days oral (cefixime). Study on patients with age group of 18-60 years both males & females with no co-morbid condition posted for laproscopic cholecystectomy for gall bladder stones. Wound inspection done on 3rd, 5th, and 7th day. RESULTS: 1 day pre-operative antibiotic is almost as effective as to multiple dose antibiotics.Hence a single-day prophylaxis is recommended to reduce the financial burdens, the emergence of resistant strains and avoid the side effects of the drugs.However , it is of utmost importance that complete asepsis be maintained during the surgery and post-operative care, irrespective of the antibiotic prophylaxis, to achieve the most desired goal of elimination of post-operative infections, thus reducing the morbidity and mortality. CONCLUSION:Single dose antibiotic is sufficient in preventing wound infection and also some other factors like proper preoperative skin preparation, sterile surgical practice & operative theatre & good postoperative nursing care to be taken care of. Prolonged administration of antibiotics is unnecessary and costlier. Prolonged use of antibiotics is associated with emergence of resistant strains and super-infections, which can be prevented by cost-effective short term antibiotic prophylaxis.